2020
DOI: 10.1101/2020.12.19.423626
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Automation of Leaf Counting in Maize and Sorghum Using Deep Learning

Abstract: Leaf number and leaf emergence rate are phenotypes of interest to plant breeders, plant geneticists, and crop modelers. Counting the extant leaves of an individual plant is straightforward even for an untrained individual, but manually tracking changes in leaf numbers for hundreds of individuals across multiple time points is logistically challenging. This study generated a dataset including over 150,000 maize and sorghum images for leaf counting projects. A subset of 17,783 images also includes annotations of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 62 publications
(88 reference statements)
0
3
0
Order By: Relevance
“…7B: RMSE = 1.29 vs RMSE = 2.62 for Phenomenal). Our method therefore avoids the bias that may occur in other leaf counting methods [Miao et al, 2021; Zhou et al, 2021; Souza and Yang, 2021] that do not take into account the disappearance of bottom leaves due to senescence. However, this trait was still consistently underestimated (bias = −1.09, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…7B: RMSE = 1.29 vs RMSE = 2.62 for Phenomenal). Our method therefore avoids the bias that may occur in other leaf counting methods [Miao et al, 2021; Zhou et al, 2021; Souza and Yang, 2021] that do not take into account the disappearance of bottom leaves due to senescence. However, this trait was still consistently underestimated (bias = −1.09, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…While the above detection methods are designed for specific cultivars in particular environments, they may not accurately distinguish tassels at early tasseling stages, making it difficult to continuously monitor maize breeding requirements. Miao et al (2021) found that the convolutional neural network-based regression counting method had poor accuracy and high bias for plants with extreme leaf counts, while the count-by-detection method based on the Faster R-CNN object detection model achieved near-human performance for plants where all leaf tips are visible. However, the two-stage detection network used in the count-by-detection method ignores the real-time requirements of field applications.…”
Section: Introductionmentioning
confidence: 99%
“…This focus on monocotyledons probably occurred because their morphological structure is relatively simple, and the difficulty of image acquisition and data analysis is relatively low. Leaf counting has been realized in maize, sorghum, and other monocotyledons over the entire growth period (Miao et al, 2021). However, studies on the leaves of dicotyledonous species such as soybean and cotton have focused only on comprehensive indicators such as canopy coverage and compactness due to the severe occlusion between leaves and complex plant types (Moreira et al, 2019;Li et al, 2020), which has led to the loss of many details.…”
Section: Introductionmentioning
confidence: 99%